Data cryptography based on musical notes on a fingerboard along with a dice - Asis Kumar Tripathy; Tapan Kumar Das; Navaneethan C (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The security of an online system is the foremost necessity nowadays. With huge growth of the IT power and with the invention of new technologies, the number of threats a user faces is growing exponentially. Cryptography is a combination of security engineering and mathematics. It is the best technology for securing distributed systems. Cryptography consists in processing plain information by applying a cipher and producing encoded output, unknown to a third-party who does has no idea about the key. In cryptography both encryption and decryption phase are processed by one or more keys. Encryption is extremely important for a safe and secure environment for the computers and the Internet.